PERAN STRATEGI SUMBER DAYA MANUSIA SEBAGAI MEDIASI PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI (STUDI PADA BALAI MONITOR SPEKTRUM FREKUENSI RADIO KELAS I SURABAYA) - Citraningtyas, Ifit; Yunikewaty, Yunikewaty; Husnatarina, Fitria (STKIP Persada Khatulistiwa Sintang, 2025)
This research aims to know the mediating role of human resource (HR) strategy in the relationship between organizational culture and employee performance at the Balai Monitor SFR Kelas I Surabaya. Amid the shift in human resource management from individual operational efficiency to overall organizational effectiveness, this study evaluates how strategic HR practices influence organizational outcomes. Using a quantitative approach and the population in this study was all employees of the Class I Surabaya Radio Frequency Spectrum Monitoring Center, totaling 128 people. Determination of the number of samples was carried out using Isaac's sample determination table and obtained 97 employees. The study employs Partial Least Squares (PLS) analysis to test hypotheses regarding the direct and indirect relationships between organizational culture, HR strategy, and performance. The findings show that HR strategy significantly mediates the influence of organizational culture on employee performance, underscoring the importance of aligning HR functions with organizational goals. This study provides insights for public sector organizations seeking to improve performance through strategic HR initiatives and highlights the importance of building an adaptive organizational culture. These findings reinforce that organizations that can build a strong, participatory, and results-oriented work culture will create an environment conducive to the development of adaptive and quality HR strategies.